Pelletization and density optimization of oil palm empty fruit bunch pellet for biomass energy - Nur Adlin Aziz (2020)
Considering the global energy crisis affecting global consumers in terms of fossil fuel insufficiency and specific interest in inventing alternative sources of renewable energy. This study was conducted to identify the key factors affecting pelletization process of Oil Palm Empty Fruit Bunches based on particle size, pelletizing pressure and test speed. The size and mass of compressed pellet were measured to calculate the pellet density. The pelletization process have been carried out within the pelletizing pressure from 7 to 21 kN by using compression force of Universal Testing Machine (UTM) with a test speed at 2 to 8 mm/min. In brief, this study focusing on the optimization of the pellet density by using response surface method (RSM), Box-Behnken Model due by using particle size, pressure and test speed as the factor tested. The density pellet identified to be increase radically and then gradually with a higher pelletizing pressure. This study proven that for lowest optimum density value occurs at particle size of 500µm, pressure of 7kN and with a test speed 2mm/min. In conclusion, with a low density of pelletized OPEFB could aid towards the transportation and packaging of the pellet in order to meet the pellet market in future.